Pemetaan Partisipatif Batas Administrasi Dusun di Desa Singajaya, Kecamatan Jonggol, Kabupaten Bogor, Provinsi Jawa Barat: Pemetaan Partisipatif Batas Administrasi Dusun di Desa Singajaya, Kecamatan Jonggol, Kabupaten Bogor, Provinsi Jawa Barat - Puspo, Tiara Ramadhanti; Saputro, Redo; Sulistya, Aryana Rachmad; Ramlah; Sari, Yetti Anita; Hayati, Kemala; Wibowo, Aryo; Shabina, N. Izza Putri; Palupi, Ahmad Rafli (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2024)
Mapping details related to village (hamlet) boundaries needs to be implemented. Problems that often occur within the villages include: problems of village administrative boundaries, then problems in the form of village facility assets that are not properly registered ( inventarisation). One of the objectives of village mapping is to accelerate the process of digitising village data by presenting it on one map. The method used was participatory mapping, which directly involved the indigenous people of Singajaya Village. Participatory mapping serves to enrich the data collected in relation to the boundaries between hamlets in Singajaya Village. The village mapping in the form of hamlet administration was processed using GIS processing, with the results being that of the total area of Singajaya Village of 555.64 Hectares, Hamlet 1 has the largest area, followed by Hamlet 4, while Hamlet 2 has the narrowest area among the hamlets in Singajaya Village. The boundaries used as benchmarks between hamlets in Singajaya Village consist of natural and artificial benchmarks, such as trees, rivers, irrigation, and roads.